DEVELOPING SPINNING WHEEL AND FLASH CARD MEDIA ON DESCRIPTIVE TEXT TO TEACH VOCABULARY FOR STUDENTS OF SMK DARUL HUDA BLITAR - Dimas Bayu Surya Mahendra; Siti Rofi'ah; Ahmad Saifudin (PROJECT (Professional Journal of English Education), 2023)
Media in the process of learning English is very important. In this study, this was evidenced by a needs analysis of 11 students and 1 English teacher in class X for students majoring in Visual Communication Design. This study aims to determine the needs of students and also to know the results of the development of instructional media on descriptive text material. This study used several ADDIE Research and Development (R&D) models to obtain results using observation instruments and unstructured interviews. It uses steps including (1) needs analysis, (2) product design, (3) development, (4) implementation (5) evaluation. The research subjects were 11 students of class X Visual Communication Design at Darul Huda Vocational School. The limitation of this research is developing spinning wheel and flash card learning media on descriptive text material for class X students majoring in Visual Communication Design. Researchers get valid results in two aspects and one very valid result. For very valid results in terms of total language (85%) and for 2 valid aspects are content (80%) and media (75%) and are suitable for use as learning media in descriptive text material. According to the satisfaction questionnaire about this product, the percentage of about 40% agreed and 60% strongly agreed. Finally, this learning The media can be used as an additional learning media for class X students majoring in Visual Communication Design.Â Keywords:Â  Spinning Wheel and Flash Card; Descriptive Text; ADDIE ResearchÂ